Development And Evaluation Of A Herbal Formulation With Antidiabetic Potential - Shahare, H.V.; Jadhav, R. R.; Ghangale, P. R.; Jejurkar, T.V.; Pandhare, S. G.; Burad, A. R.; Bedmutha, S. S.; Jain, K. M. (Journal of Neonatal Surgery, 2025)
The present work involves the Formulation of Antidiabetic Herbal Biscuit. Herbal biscuits have been researched for their potential antidiabetic effects. Some studies have shown that certain herbs, such as fenugreek and cinnamon, which are commonly used in herbal biscuits, may have hypoglycemic (blood sugar-lowering) effects and can help improve insulin sensitivity in individuals with type 2 diabetes. For Formulation of Herbal Biscuit, we used oven and for evaluation we perform quantitative test of Carbohydrates, Protein, Starch, Amino acid. The Evaluation and Formulation of antidiabetic herbal biscuit were performed and it contains carbohydrates, protein, Amino acid and starch.